Evaluation Of the Emergency Severity Index Triage For Improving Emergency Room Services Quality In Indonesian Hospital - Ramli, Hasnah; Erfina, Erfina; Rini Rachmawaty (YCAB Publisher, 2024)
Background:Effective prioritization is crucial in delivering high-quality emergency medical services, although it is often lacking. Objective:This study aims to evaluate the application of triage based on the Emergency Severity Index (ESI) in improving the quality of emergency departments in hospitals in Indonesia. Methods:An accidental sample of 100 emergency room patients was selected. Patient satisfaction was measured using questionnaires, while infrastructure, support facilities, and the triage process were assessed through direct observation. Results:The evaluation found that nurse staffing levels did not meet standards and were inadequate to meet patient needs. Triage facilities and infrastructure at both hospitals met established standards. The triage process, conducted on 100 respondents by 30 nurses, revealed that the majority of patients were categorized as ESI level 3, comprising 82 (82%) respondents. There was an excessive use of triage resources beyond projections, and patient placement did not always adhere to standards, although the average response time was within the accepted range. Patient satisfaction was evaluated across five dimensions; the most satisfying dimensions were assurance and empathy, with 90% of respondents rating thempositively, while the tangibles dimension received the lowest satisfaction rating at 84%. The correlation between the application of ESI triage and patient satisfaction was not statistically significant (p-value = 0.101, higher than 0.05). Conclusion:It is recommended that hospitals increase the number and competence of nursing staff in emergency departments to ensure response times and patient placement align with ESI triage standards, thereby enhancing the effectiveness of triage implementation. Keywords:emergency severity index triage; quality of care; emergency department